Adiposopathy and Obesity Paradox - Indriyanti Rafi Sukmawati; Andi Wijaya (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Obesity has reached global epidemic proportions in both adults and children and is associated with numerous comorbidities, including hypertension, type 2 diabetes mellitus (T2DM), dyslipidemia and major cardiovascular diseases (CVD).CONTENT: Adiposity may cause adipocyte and adipose tissue anatomic and functional abnormalities, termed adiposopathy (adipose-opathy) or "sick fat," that result in endocrine and immune derangements. Adiposopathy may directly contribute to CVD through pericardiac and perivascular effects on the myocardium and blood vessels. Adiposopathy may also indirectly contribute to CVD through promoting or worsening major CVD risk factors such as T2DM, high blood pressure, and dyslipidemia. Despite this adverse association, numerous studies have documented an obesity paradox in which overweight and obese people with established CVD, including hypertension, heart failure, coronary heart disease, and peripheral arterial disease, have a better prognosis compared with nonoverweight/nonobese patients. These paradoxical findings are made less paradoxical when the pathogenic potential of excessive body fat is assessed based on adipose tissue dysfunction rather than simply on increased fat mass alone.SUMMARY: Adiposopathy is defined as pathological adipose tissue function that may be promoted and exacerbated by fat accumulation (adiposity) and sedentary lifestyle in genetically susceptible patients. Adiposopathy is a root cause of some of the most common metabolic diseases observed in clinical practice, including T2DM, hypertension and dyslipidemia.KEYWORDS: adiposopathy, adiposity, obesity paradox, adipocyte dysfunction, adipose hypertrophy, adipose hyperplasia